Raman scattering of internal dynamics in spinel Zn2TiO 4 nanostructures - Wongratanaphisan D. (2014)
We present here the results of the Raman study of lattice dynamics and local compositional fluctuations in cubic spinel Zn2TiO4 nanostructures. The observed Raman modes of the spinel structure are identified and attributed to local vibrational modes. Additionally, the analysis of the nonpolar E2(H) (∼437 cm-1, 54.2 meV) and A 1g (∼716 cm-1, 88.7 meV) modes are made and contributed to lattice deformation associated with the distinct coordination preferences of Zn and Ti. Copyright © Taylor & Francis Group, LLC.